Development of computer graphics algorithm for manipulation of image file / Norraidah Zunaidak - Zunaidak, Norraidah (1995)
This project explores the software development of image data compression and decompression techniques. Two techniques implemented here are Huffman coding technique and Run Length Encoding technique. The development of computer graphics and image processing techniques in many applications related to scientific, engineering and medical fields cause an interest to combine graphic techniques and image processing techniques[l 5]. The other purpose of this project is to manipulate the decompressed images by development of computer graphic using C++ in windows environment The software has the ability to manipulate, the images of common format like PCX and BMP.